2002
DOI: 10.1086/344322
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to Placental Malaria. IV. Placental Malaria Is Associated with Up‐Regulation of Macrophage Migration Inhibitory Factor in Intervillous Blood

Abstract: Macrophage migration inhibitory factor (MIF) may play a role in immune responses to malaria during pregnancy by virtue of its ability to activate macrophages and to overcome the immunosuppressive effect of glucocorticoids. The present study investigated whether plasma MIF levels are altered in pregnant women with placental malaria (PM) and/or human immunodeficiency virus (HIV) infection. For the first time it is demonstrated that MIF levels in the intervillous blood (IVB) plasma were significantly elevated, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 14 publications
4
52
0
1
Order By: Relevance
“…Our studies demonstrated that MIF is elevated 300 to 500 fold in placental intervillous blood (IVB) plasma compared to peripheral blood plasma (9). In PM-positive women, there was a significant increase in IVB MIF levels compared to PMnegative women.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Our studies demonstrated that MIF is elevated 300 to 500 fold in placental intervillous blood (IVB) plasma compared to peripheral blood plasma (9). In PM-positive women, there was a significant increase in IVB MIF levels compared to PMnegative women.…”
mentioning
confidence: 68%
“…A double sandwich enzyme-linked immunosorbent assay was used to measure MIF levels in culture supernatants as previously described (9). MIF was detected with a capture mouse monoclonal anti-human MIF antibody (clone 12302.2) and a biotinylated goat anti-human MIF antibody from R&D Systems, Inc. (Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15, 17-20 Consistent in its role as mediator of innate immunity and inflammation, MIF is induced in various infections, including those that occur during pregnancy. 15,18 There is a lack of data in humans on the alteration of MIF in psychological stress or other behavioral risk factors for preterm delivery. Studies in vitro and experimental animals suggest that MIF secretion is induced by psychological stress, and the stress hormone, corticotropin releasing hormone (CRH), 10, 21 Thus MIF is linked with infections, reproductive function, and psychological stress, but the details of how MIF may participate in PTD are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Migration inhibitory factor (MIF) merangsang fagositosis eritrosit terinfeksi juga mendorong akumulasi makrofag di plasenta [38]. Konsentrasi MIF lebih tinggi pada ibu hamil primigravida dari pada multigravida disebabkan karena kadar steroid pada primigravida lebih tinggi, oleh karena itu peningkatan konsentrasi MIF dapat memberikan perlindungan pada plasenta [39].…”
Section: Repon Imun Terhadap Infeksi Malaria Selama Kehamilanunclassified